Participation of Foreign Graduate Students in Campus-Based Non-Formal Education Programmes in Universiti Putra Malaysia - Amadhila, Helena Naitsuwe (2008)
This study examined participation in campus based non-formal education programmes among foreign graduate students in Universiti Putra Malaysia and its correlates. Specifically, the study (1) determined the level of participation of UPM foreign graduate students in campus based non-formal education programmes, (2) ascertained whether there is differences in the level of participation of foreign graduate students in campus based non-formal education programmes across gender, programme of study and field of study (3) determined the relationships of the level of participation of foreign graduate students in campus based non-formal education programmes with general health, time engagement, knowledge about campus based non-formal education programmes, attitude toward participating in campus based non-formal education programmes, self-esteem and behavioural intention to participate (4) and determined the contribution of selected independent variables on level of participation in campus based non-formal education programmes The data were collected through survey using self-administered questionnaire. A total of 178 UPM foreign graduate students participated in the study. Descriptive and inferential statistics were used to analyse the data. The survey showed that the level of participation of UPM foreign graduate students in campus based non-formal education programmes was relatively quite low. However, some campus based non-formal education programmes, particularly academic related such as thesis writing, were preferred more than other campus based non-formal education programmes. Level of participation in campus based non-formal education program is significantly and positively correlated with general health, knowledge about campus based non-formal education programmes, attitudes toward participating in campus based non-formal education programmes, self-esteem, behavioural intention to participate, and programme of study. These variables explained about 13.3% of the variance in the level of participation of UPM foreign graduate students in campus based non-formal education programmes. Thus, campus based non-formal education programmes should be regarded as an important networking support system for UPM foreign graduate students to successfully adjust to the university environment and culture. The study provides understanding of tentative model of participation for further testing.